Dampak Objek Wisata Religi Terhadap Pendapatan Dan Peluang Usaha Pedagang Disekitar Makam Kh. Muhammad Zainuddin Abdul Madjid - Charisma Rindayani; Muhammad Zainul; Susilawati Susilawati; M. Affan Ghazali; Meinatul Maulidian; Tamzil Amrol Aen (Universitas Hamzanwadi, 2024)
This study was conducted to: 1) To analyze the development of religious tourism objects in the area of ​​the Tomb of KH. Muhammad Zainuddin Abdul Madjid. 2) To analyze the impact of the development of religious tourism objects on the income and business opportunities of traders. This study uses a qualitative descriptive research method. Primary and secondary data are used to collect data sources. This study collected respondents through a purposive sampling method. With this technique, 15 village governments, tourism managers, and communities were selected as informants in this study. The results of the study show that: 1) The development of religious tourism destinations at the Tomb of Maulana Syaikh continues to experience an increase in the development of existing facilities and infrastructure. The government built the Tomb of Maulana Syaikh as a halal tourist destination and follows tourism standards, such as providing worship facilities such as mosques, halal food and drinks, and public facilities such as toilets with clean water, rest areas for visitors, abror canteens, museums. 2) This religious tourism object can increase the income of traders more than before and open up many business opportunities for sellers around the Tomb of Maulana Syaikh. With increased income and business opportunities available to traders, their well-being is expected to improve. The Maulana Syaikh Tomb has experienced an impact, with an increase in the average daily income of traders ranging from Rp 200,000 to Rp 500,000 per day. For example, on major holidays, traders' income is even higher, around Rp 1,000,000 to Rp 2,500,000 compared to normal days.